POTENTIAL ANALYSIS AND DEVELOPMENT STRATEGY FOR COMMUNITY-BASED SUSTAINABLE TOURISM IN LANGGAHAN VILLAGE, KINTAMANI - I Wayan Kiki Sanjaya; Made Arya Astina (Lafadz Jaya Publisher, 2023)
Langgahan Village is one of the villages in the Kintamani area, Bali which has a variety of tourism potential. However, currently, only one destination is being developed in the village, namely Pelisan Waterfall. The purposes of this study are to identify and map the tourism potential in Langgahan Village to be developed as a sustainable tourism destination based on community-based tourism (CBT). This research was conducted by using a qualitative descriptive research approach. Data were collected through observation, interviews, and literature study. The interview involved the Head of Langgahan Village, the Head of the Tourism Awareness Group, tourists, and tourism industry players. Data analysis was carried out using SWOT analysis, the results of which were described objectively and clearly. The results of the analysis show that Langgahan Village has the potential for natural and cultural tourism but does not have the potential for man-made tourism. The natural tourism potential in Langgahan Village is the Pelisan waterfall, orange and coffee plantations, and pine forests. While the potential for cultural tourism owned by Langgahan Village is the Melukat ceremony and religious and customary ceremonies. This potential can be developed by implementing CBT-based strategies, namely (1) involving the entire community in planning, developing, and managing tourism in Langgahan Village, (2) organizing tourism training for the community, (3) developing promotional media by optimizing social media and media. other digital services, (4) involving other parties in promoting, such as travel agents, (5) improving infrastructure and access to Langgahan Village, and (6) drafting regulations or regulations to protect natural and cultural resources.